Oedipus the king - Sophocles; Taylor, Don. (Princeton, N.J. Films for Humanities and Sciences, c1986., 1986)
A play performed by the British classical actors recounting the beginning of the Odipus saga, setting the stage and creating the characters who will continued the story to its conclusion in Antigone.
VHS.
Keywords: Oedipus (Greek mythology) -- Drama; Tragedies